Advances in Computer Science and IT - M Akbar Hussain, D (IntechOpen, 2009)
The book presents some very interesting and excellent articles for this divergent title. The 22 chapters presented here cover core topics of computer science such as visualization of large databases, security, ontology, user interface, graphs, object oriented software developments, and on the engineering side filtering, motion dynamics, adaptive fuzzy logic, and hyper static mechanical systems. It also covers topics which are combination of computer science and engineering such as meta computing, future mobiles, colour image analysis, relative representation and recognition, and neural networks. The book will serve a unique purpose through these multi-disciplined topics to share different but interesting views on each of these topics.